A selective defect in the glial wedge as part of the neuroepithelium disruption in hydrocephalus development in the mouse hyh model is associated with complete corpus callosum dysgenesis - Rodríguez-Pérez, Luis-Manuel; López-de-San-Sebastián, Javier; de Diego, Isabel; Smith, Aníbal; Roales-Buján, Ruth; Jiménez, Antonio J.; Paez-Gonzalez, Patricia (Frontiers in Cellular Neuroscience, 2024)
Dysgenesis of the corpus callosum is present in neurodevelopmental disorders and coexists with hydrocephalus in several human congenital syndromes. The mechanisms that underlie the etiology of congenital hydrocephalus and agenesis of the corpus callosum when they coappear during neurodevelopment persist unclear. In this work, the mechanistic relationship between both disorders is investigated in the hyh mouse model for congenital hydrocephalus, which also develops agenesis of the corpus callosum. In this model, hydrocephalus is generated by a defective program in the development of neuroepithelium during its differentiation into radial glial cells. In this work, the populations implicated in the development of the corpus callosum (callosal neurons, pioneering axons, glial wedge cells, subcallosal sling and indusium griseum glial cells) were studied in wild-type and hyh mutant mice. Immunohistochemistry, axonal tracing experiments, and organotypic cultures from normal and hyh mouse embryos were used. Our results show that the defective program in the neuroepithelium/radial glial cell development in the hyh mutant mouse selectively affects the glial wedge cells. The glial wedge cells are necessary to guide the pioneering axons as they approach the corticoseptal boundary. Our results show that the pioneering callosal axons arising from neurons in the cingulate cortex can extend projections to the interhemispheric midline in normal and hyh mice. However, pioneering axons in the hyh mutant mouse, when approaching the area corresponding to the damaged glial wedge cell population, turned towards the ipsilateral lateral ventricle. This defect occurred before the appearance of ventriculomegaly. In conclusion, the abnormal development of the ventricular zone, which appears to be inherent to the etiology of several forms of congenital hydrocephalus, can explain, in some cases, the common association between hydrocephalus and corpus callosum dysgenesis. These results imply that further studies may be needed to understand the corpus callosum dysgenesis etiology when it concurs with hydrocephalus.